2009
DOI: 10.1007/s12648-009-0003-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of unfolding on the thickness of the hydration layer of a protein

Abstract: Properties of water in the hydration layer around a protein is intimately correlated with its function. A knowledge of the thickness of the hydration layer is important to understand its role in guiding the foldingunfolding of the protein. We have performed atomistic molecular dynamics simulations of the folded native and a partially unfolded molten globule structure of the villin headpiece subdomain or HP-36 in aqueous solution to estimate the effect of unfolding on the thickness of hydration layer around dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
(95 reference statements)
1
0
0
Order By: Relevance
“…The calculations are carried out by considering those water molecules that are present within a distance of 5 Å from the surface of different segments of barstar (α-helices, β-sheet, and the interconnecting loops). This is consistent with earlier reports , where it is shown that the effects of a protein on water dynamical properties are primarily restricted to those that are present in its first hydration layer (within ∼5 Å). The results reported are based on calculations over the equilibrated trajectories as obtained from simulations S1, S2, and S3.…”
Section: Resultssupporting
confidence: 93%
“…The calculations are carried out by considering those water molecules that are present within a distance of 5 Å from the surface of different segments of barstar (α-helices, β-sheet, and the interconnecting loops). This is consistent with earlier reports , where it is shown that the effects of a protein on water dynamical properties are primarily restricted to those that are present in its first hydration layer (within ∼5 Å). The results reported are based on calculations over the equilibrated trajectories as obtained from simulations S1, S2, and S3.…”
Section: Resultssupporting
confidence: 93%